POTENTIAL IMMUNOGENICITY OF BACTERIA Aeromonas hydrophila GPL-05 AND GL-02 STRAINS AS A CANDIDATE VACCINES - Dini Siswani Mulia; Ani Khusniah; Heri Maryanto (AQUASAINS, 2015)
Aeromonas hydrophila is very potential to be used in vaccines and disease control MAS (Motile Aeromonas Septicemia) caused by the bacteria. However, strains of A. hydrophila bacteria which have high immunogenicity limited. Not to mention, in the field often decrease the pathogenicity of the bacteria as vaccine material resulting in a decrease in the immunogenicity of a vaccine made. Therefore, it is necessary to inventory and collecting strains of A. hydrophila bacteria potentially good that vaccination continuity can be maintained. This study used an experimental method with a completely randomized design (CRD), with treatments such as P1: A. hydrophila vaccine strain GPL-05; P2: A. hydrophila vaccine strain GL-02; and P3: control (PBS), with five replicates.This study aims to assess the potential immunogenicity A.hydrophila bacterial strains as vaccine candidates. Test fish used is African catfish was about 2 months with a length of 10-15 cm and width 15-20 g. The main parameters are observed antibody titer and cross-reaction test, while supporting parameters are parameters of water quality include water temperature, pH, dissolved oxygen. Antibody titer data was analyzed by Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at the test level of 5%, while the data and the results of cross-reaction of water quality parameters observed descriptively. The results showed that the bacteria A. hydrophila strain GPL-05 and GL-02 has a high immunogenicity, thus recommended a candidate vaccine.